2019
DOI: 10.1088/1742-6596/1374/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Production and Optimization of Lipase by Aspergillus niger using Coconut Pulp Waste in Solid State Fermentation

Abstract: Lipase has high economical value and an attribute that treasures wide range applications. Among the microbes, fungi to be the best source for lipase production in agro-industrial residue using solid state fermentation (SSF). One of agro-industrial residue is coconut pulp waste. The aims of this study is to explore the possibility of coconut pulp waste for producing of lipase using fungi isolate, Aspergillus niger and find the partial optimum condition of lipase production based on 2 parameters only. The crude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Optimal inoculum size has a significant role in the fermentation process; meanwhile, the aggregation of spores can retard the progression and development of the microorganism [29]. Our findings show similarity with Suyanto et al [30], who reported that the optimum lipase activity for Aspergillus niger was obtained at a spore concentration of 1 × 10 6 spore mL −1 . Previous studies also demonstrated that 83.33% lipase activity was obtained by 1% (v/v) inoculum in addition to the production medium.…”
Section: Optimization Of Parameters By Rsmsupporting
confidence: 89%
“…Optimal inoculum size has a significant role in the fermentation process; meanwhile, the aggregation of spores can retard the progression and development of the microorganism [29]. Our findings show similarity with Suyanto et al [30], who reported that the optimum lipase activity for Aspergillus niger was obtained at a spore concentration of 1 × 10 6 spore mL −1 . Previous studies also demonstrated that 83.33% lipase activity was obtained by 1% (v/v) inoculum in addition to the production medium.…”
Section: Optimization Of Parameters By Rsmsupporting
confidence: 89%
“…This approach provides a stable environment for the growth and production of lipases by fungi . The SSF utilizing Aspergillus niger yielded crude lipase with an activity of 10.83 U/mL . The production of fungal lipase is significantly influenced by the nitrogen source.…”
Section: Resultsmentioning
confidence: 99%
“… 34 The SSF utilizing Aspergillus niger yielded crude lipase with an activity of 10.83 U/mL. 35 The production of fungal lipase is significantly influenced by the nitrogen source. Wheat bran comprises 13.1 ± 1.3% protein on average, and several authors have reported it as a protein-rich solid substrate for the production of fungal lipase.…”
Section: Resultsmentioning
confidence: 99%
“…This fungus is a perfect candidate for largescale enzyme production because it can flourish in a variety of environments [36]. The efficient and economical production of lipase for use in various biotechnological and industrial processes can be facilitated by utilizing the enzymatic potential of Aspergillus niger [37].…”
Section: Resultsmentioning
confidence: 99%